Studi Kualitatif Pemahaman Perawat Intensive Care Unit tentang Pengkajian Nyeri Behaviour Pain Scale - Fatimah Khoirini; Rahma Annisa (JURNAL KEPERAWATAN RAFLESIA, 2019)
Assessment is the initial nursing process. In the nursing assessment obtained information about patient data used as a baseline and determine the next stage. Patients in intensive rooms with ventilators often received nursing actions that cause pain. Pain assessment in patients using ventilators must use special assessment techniques. Patients with ventilators require standardized assessment methods because they cannot communicate the pain they feel verbally. Payen in 2001 developed the Behavioral Pain Scale (BPS). Critical patients who are fitted with ventilators need a systematic and consistent assessment of pain. Understanding is the ability to explain correctly and in detail about something. Before performing an action properly one needs to understand the action. This study aimed to determine the experience and understanding of ICU nurses about pain assessment using BPS at M Yunus Bengkulu General Hospital. This study used the qualitative study that focus on disclosing nurses' understanding of pain assessment using BPS. Themes that emerged in this study were 1. use BPS, 2. Three items in the BPS assessment, 3. Indicators assessing pain, 4. Maximum minimum scoring, 5. Range of pain values. Nurse’s understanding about BPS was very necessary.